Volume Changes in Brain Subfields of Patients with Alzheimer’s Disease After Transcranial Ultrasound Stimulation - Sheng-Yao Huang; Meng-Ting Wu; Chung-Fu Sun; Feng-Yi Yang (Diagnostics)
Background/Objectives: Alzheimer’s disease (AD) is characterized by progressive brain atrophy marked by cognitive decline and memory loss, which significantly affect patients’ quality of life. Transcranial ultrasound stimulation (TUS) is a potential physical treatment for AD patients. However, the specific brain regions stimulated by TUS and its therapeutic effects remain unclear. Methods: In this study, magnetic resonance imaging (MRI) and FreeSurfer segmentation were employed to assess alterations in the brain volume of AD patients after TUS. Results: Our findings revealed significant volume increases in the corpus callosum (CC) and lateral orbitofrontal cortex (lOFC) in the TUS group. Moreover, the volumetric changes in the CC were strongly correlated with improvements in the Mini-Mental State Examination score, which is a widely used measure of cognitive function of AD patients. Conclusions: TUS has the potential to alleviate disease progression and offers a non-invasive therapeutic approach to the improvement of cognitive function in AD patients.